2021
DOI: 10.1364/oe.427541
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the chaotic dynamics of a semiconductor nanolaser subjected to FBG feedback

Abstract: Nonlinear dynamics of semiconductor nanolasers subjected to distributed feedbacks from fiber Bragg grating (FBG) are investigated through modified rate equations, which include the unique Purcell cavity-enhanced spontaneous emission factor F and spontaneous emission coupling factor β. In the analysis, the effects of F, β, frequency detuning, feedback strength, feedback delay, FBG bandwidth and length on chaotic performance are evaluated. It is observed that the approach of FBG feedback outperforms mirror feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…This investigation involved the modification of rate equations, incorporating variables such as F and β. Our findings revealed that employing FBG feedback surpasses mirror feedback in its ability to conceal TDSs and expand effective bandwidth, especially when selecting intermediate feedback strength and frequency detuning, as described in reference [55]. Therefore, these studies have provided evidence that NLs, similar to traditional SLs, exhibit an extensive array of dynamic characteristics.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…This investigation involved the modification of rate equations, incorporating variables such as F and β. Our findings revealed that employing FBG feedback surpasses mirror feedback in its ability to conceal TDSs and expand effective bandwidth, especially when selecting intermediate feedback strength and frequency detuning, as described in reference [55]. Therefore, these studies have provided evidence that NLs, similar to traditional SLs, exhibit an extensive array of dynamic characteristics.…”
Section: Introductionsupporting
confidence: 52%
“…Hence, in recent years, the application of this type of laser in chaotic systems has been extensively investigated by a multitude of researchers. They have proposed several theoretical models of innovative semiconductor NLs to explore nonlinear dynamics [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and TDS concealment [53][54][55]. In these systems, the dynamic properties of NLs are significantly influenced by two crucial parameters: the Purcell factor F and the spontaneous emission coupling factor β [53].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they have attracted significant attention in recent years. Scholars have proposed various theoretical models of semiconductor NLs to study their dynamic characteristics [30][31][32][33][34][35][36][37][38][39] and TDS concealment [40][41][42]. Among them, the TDS concealment mechanism in ring networks based on NLs has not been explored.…”
Section: Introductionmentioning
confidence: 99%